2013
DOI: 10.3126/kumj.v10i2.7355
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Management of a Patient with Dermatomyositis and Valvular Heart Disease

Abstract: Dermatomyositis is an idiopathic inflammatory myopathy with involvement of muscle, skin and other organs. Valvular heart disease increases the risk of perioperative adverse cardiac events. Only a little information is available about the anaesthetic management of a patient with dermatomyositis and valvular heart disease. Here we considered combined spinal-epidural technique for total abdominal hysterectomy, minimizing the risk of delayed recovery from muscle relaxants, aspiration pneumonitis, arrhythmias and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
2
0
5
Order By: Relevance
“…Los relajantes musculares por lo tanto, pueden tardar más en alcanzar la unión neuromuscular, lo que da lugar a un inicio de acción más lento y un período de reversión más largo [1], [4]. No hay que olvidar que muchos de estos pacientes presentan patologías malignas que por sí mismas ya afectan a la transmisión neuromuscular [3], [5].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Los relajantes musculares por lo tanto, pueden tardar más en alcanzar la unión neuromuscular, lo que da lugar a un inicio de acción más lento y un período de reversión más largo [1], [4]. No hay que olvidar que muchos de estos pacientes presentan patologías malignas que por sí mismas ya afectan a la transmisión neuromuscular [3], [5].…”
Section: Discussionunclassified
“…El empleo de los reversores de los relajantes es controvertido. Algunos autores describen que pueden causar mayor debilidad muscular y disritmias [5].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…17 Further, Shrestha GS et al have reported a case describing the safety and efficacy of combined epidural spinal in a patient of dermatomysitis with valvular heart disease undergoing total abdominal hysterectomy. 18 There may be other problems complicating the anaesthetic management. Cardiac dysfunction, if present is mainly because of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are supposed to be sensitive to nondepolarizing muscle relaxants, and use of their antagonist drugs may cause muscle weakness and dysrhyhmias. [ 2 ] Vecuronium and pancuronium are associated with prolonged neuromuscular paralysis though atracurium has been implemented as a safe drug under neuromuscular monitoring. Neuromuscular monitoring is suggested in these patients due to lack of standard recommendations regarding to the application of nondepolarizing muscle relaxants.…”
mentioning
confidence: 99%